PERILAKU PEDULI LINGKUNGAN PADA MASYARAKAT DI DESA PENFUI TIMUR KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Jima, Maria Hilaria; Samin, Mikael; Hasan, Muhammad Husain (Universitas Nusa Cendana, 2021)
The aims of this study were: (1) to determine the environmental care behavior of the people in the East Penfui Village, Central Kupang District, Kupang Regency, (2) to determine the role of the community in environmental care behavior in the East Penfui Village, Central Kupang District, Kupang Regency. This study used a descriptive method with a quantitative approach. The type of this research was a survey. The data sources in this study were primary data and secondary data. The data collection method used observation method, the questionnaire method (questionnaire), and the documentation method. The data in this study will be processed and tabulated through a graph table. The results in the study were: (1) environmental care behavior in the community in East Penfui Village based on environmental care indicators consisting of water management/use, energy management/use, transportation use, waste management, care for the surrounding environment, and natural disaster mitigation, including in the good category. (2) the role of the community in environmental care behavior is classified as very good, because the community is very enthusiastic in maintaining cleanliness even though there are a small number of people who are not involved.